2021
DOI: 10.3389/fcell.2020.588368
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Signature Constructed by RNA-Binding Protein Coding Genes to Improve Overall Survival Prediction of Glioma Patients

Abstract: RNA binding proteins (RBPs) have been reported to be involved in cancer malignancy but related functions in glioma have been less studied. Herein, we screened 14 prognostic RBP genes and constructed a risk signature to predict the prognosis of glioma patients. Univariate Cox regression was used to identify overall survival (OS)-related RBP genes. Prognostic RBP genes were screened and used to establish the RBP-signature using the least absolute shrinkage and selection operator (Lasso) method in The Cancer Geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…[ 31 ] Another study also suggested that ISG20 expression was inversely associated with survival in glioma patients. [ 14 ] In this study, our results were consistent with these conclusions. For the RBP FTSJ2, previous studies had shown that it had heat shock protein properties and was considered as a tumor suppressor gene in lung cancer.…”
Section: Discussionsupporting
confidence: 92%
“…[ 31 ] Another study also suggested that ISG20 expression was inversely associated with survival in glioma patients. [ 14 ] In this study, our results were consistent with these conclusions. For the RBP FTSJ2, previous studies had shown that it had heat shock protein properties and was considered as a tumor suppressor gene in lung cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, this combination therapy may be a promising treatment approach for high-risk patients with LGG based on our signature. In the KEGG analysis, the risk signature was associated with ECM-receptor interaction and focal adhesion, suggesting that the two glioma subgroups may differ in their ability to invade and migrate ( 47 , 48 ). In addition, the DEGs were significantly enriched in several cancer-related pathways, such as mitogen-activated protein kinase (MAPK), p53, and Wnt signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The primary SPA17 and beta-tubulin rabbit polyclonal antibodies were obtained from the Proteintech company (13367-1-AP, 10094-1-AP), and the concentrations of antibodies were entirely following their specifications. The western blot assay was carried out according to the process described in our previous study ( 24 ). The agents and related kits used in this research were consistent with the previous study.…”
Section: Methodsmentioning
confidence: 99%